Retracted: Gastrodin relieves inflammation injury induced by lipopolysaccharides in MRC‐5 cells by up‐regulation of miR‐103. Issue 2 (25th November 2019) - Xi, Zhuona; Qiao, Yahong; Wang, Jifang; Su, Hongjian; Bao, Zhen; Li, Hongyan; Liao, Xiaoming; Zhong, Xiaolan
Abstract: The beneficial function of gastrodin towards many inflammatory diseases has been identified. This study designed to see the influence of gastrodin in a cell model of chronic obstructive pulmonary disease (COPD). MRC‐5 cells were treated by LPS, before which gastrodin was administrated. The effects of gastrodin were evaluated by conducting CCK‐8, FITC‐PI double staining, Western blot, qRT‐PCR and ELISA. Besides this, the downstream effector and signalling were studied to decode how gastrodin exerted its function. And dual‐luciferase assay was used to detect the targeting link between miR‐103 and lipoprotein receptor‐related protein 1 (LRP1). LPS induced apoptosis and the release of MCP‐1, IL‐6 and TNF‐α in MRC‐5 cells. Pre‐treating MRC‐5 cells with gastrodin attenuated LPS‐induced cell damage. Meanwhile, p38/JNK and NF‐κB pathways induced by LPS were repressed by gastrodin. miR‐103 expression was elevated by gastrodin. Further, the protective functions of gastrodin were attenuated by miR‐103 silencing. And LRP1 was a target of miR‐103 and negatively regulated by miR‐103. The in vitro data illustrated the protective function of gastrodin in LPS‐injured MRC‐5 cells. Gastrodin exerted its function possibly by up‐regulating miR‐103 and modulating p38/JNK and NF‐κB pathways.